Some Remarks on Galician Language from the So-called Franxa Leste - Gómez Bautista, Alberto (Madrygal. Revista de Estudios Gallegos, 2004)
This article examines the situation of Galician in the so-called Western Strip, arguing for the need to find an alternative to the term «External Galician», which is often used to refer to the language spoken in the Eo-Navia area, the Eastern Ancares Mountains, Western Bierzo, and As Portelas. All these areas have Galician as their original language but are now outside the administrative boundaries of the autonomous region of Galicia. Sociolinguistics, Eo-Navia, Bierzo, As Portelas, Lingüistic Normalization.